Soil quality index for paddy fields based on standard scoring functions and weight allocation method. Issue 3 (23rd February 2020) - Dengiz, Orhan
ABSTRACT: Rice ecosystems are currently impacted by numerous issues resulting in reduced returns from rice production. In order to sustainably increase rice yields, it is important to understand the soil quality of paddy fields. The aim of this study was to determine the quality of soil of the Çarşamba Deltaic Plain in Turkey for rice cultivation. For that purpose, the integrated Soil Quality Index (SQI) model, which is based on standard scoring functions and the weight assignment approach, was used. A total of 14 soil quality parameters, based on the key predictor variables for determining rice yield, were included in the SQI model by grouping them within three indicator classes, namely physical, chemical and nutrient element content. Soil samples were collected from 160 grid points in total in the study area which had been divided into 600 m × 600 m grid squares. Very high-quality soil was not detected in the study area. However, 36.1% of the soil was classified as high quality whereas 23.2% of the total area had low and very low soil quality for rice cultivation. The SQI model provides comprehensive guidance for land allocation for the cultivation of rice and potentially for other crops.